Longitudinal Bowel Behavior Assessed by Bowel Ultrasound to Predict Early Response to Anti-TNF Therapy in Patients With Crohn's Disease: A Pilot Study. (4th January 2022) - Chen, Yu-Jun; Chen, Bai-Li; Liang, Mei-Juan; Chen, Shu-Ling; Li, Xue-Hua; Qiu, Yun; Pang, Lan-Lan; Xia, Qing-Qing; He, Yao; Zeng, Zhi-Rong; Chen, Min-Hu; Mao, Ren; et al.
Abstract: Background: Early changes in bowel behavior during anti-tumor necrosis factor (anti-TNF) induction therapy in Crohn's disease (CD) are relatively unknown. We determined (1) the onset of changes in bowel behavior in CD patients receiving anti-TNF therapy by ultrasound and (2) the feasibility of shear wave elastography (SWE) in predicting early response to anti-TNF therapy. Methods: Consecutive ileal or ileocolonic CD patients programmed to initiate anti-TNF therapy were enrolled. Bowel ultrasound was performed at baseline and at weeks 2, 6, and 14. Changes in bowel wall thickness, Doppler signals of the bowel wall (Limberg score), and SWE values were compared using a linear mixed model. Early response to anti-TNF therapy was based on a composite strategy of clinical and colonoscopy assessment at week 14. Results: Of the 30 patients enrolled in this study, 20 patients achieved a response to anti-TNF therapy at week 14. The bowel wall thickness and SWE value of the response group showed a significant downward trend compared with the nonresponse group ( P = .003 and P = .011, respectively). Bowel wall thickness, the Limberg score, and SWE values were significantly reduced as early as week 2 compared with baseline ( P < .001, P < .001, and P = .003, respectively) in the response group. Baseline SWE values (21.3 ± 8.7 kPa vs 15.3 ± 4.7 kPa; P = .022) and bowel wall thickness (8.5 ± 2.3 mm vs 6.9 ± 1.5 mm; P = .027) in the nonresponse group were significantly higher than in the response group. Conclusions: This pilot study suggested that changes in bowel ultrasound behavior could be assessed as early as week 2 after starting anti-TNF therapy. Bowel ultrasound together with elasticity imaging could predict early response to anti-TNF therapy. Lay Summary: This pilot study suggested that changes in bowel ultrasound behavior could be assessed as early as 2 weeks after anti-tumor necrosis factor therapy in patients with Crohn's disease. Bowel ultrasound together with elasticity imaging could predict early response to anti-tumor necrosis factor therapy.